The Effect of Leadership Style, Compensation and Competence on Optimizing Organizational Performance - Natsir, Rahmadhany; Ramli, Mansyur; Putra, Aditya Halim Perdana Kusuma (Manunggal Halim Jaya, 2024)
The purpose of this study is to determine the influence of leadership style, compensation, and competence on the optimization of organizational performance at the Brackishwater Aquaculture Fisheries Research Institute and Fisheries Extension (BRPBAPPP) Maros. The research design is quantitative, with data analysis techniques including classical assumption tests and multiple linear regression. The results of this study demonstrate that the leadership style implemented at BRPBAPPP Maros has a significant impact on organizational performance. Effective, transparent, and communicative leadership can enhance employee motivation and productivity, ultimately leading to a positive impact on the overall performance of the organization. Additionally, a fair and competitive compensation system significantly influences organizational performance, as does employee competence. Collectively, leadership style, compensation, and competence jointly contribute significantly to the optimization of organizational performance at BRPBAPPP Maros. Enhancing leadership style, improving compensation, and developing employee competence can increase the operational effectiveness and efficiency of the organization.